Exploring the Impact of Artificial Intelligence on Language Acquisition, Linguistic Development, and Language Use: A Case Study from India - John, Aby (Forum for Linguistic Studies, 2025)
Artificial Intelligence (AI) plays a significant role in the contemporary education. Although the presence of AI is evident in foreign language teaching, studies related to its role in building Teacher-Student Rapport (TSR), Teacher Immediacy (TI) and Willingness to Communicate (WTC) is scarce. This study explores how teacher-student dynamics and students’ attitudes toward artificial intelligence intersect, shedding light on strategies to enhance engagement and motivation in language education. By integrating insights from existing research, this inquiry seeks to investigate the role of AI in fostering TSR, TI and WTC, thereby revealing the complex relationships between these variables. This study analyses these factors and bridges the existing research gap. Data collected from 50 EFL teachers and 165 EFL students in higher education institutions in two different south Indian states namely Tamil Nadu and Kerala, and data obtained through in-depth interviews with teachers who are trained to use AI for English language teaching are analyzed in this study. The questionnaire’s internal consistency and reliability were rigorously tested using Cronbach’s Alpha coefficient. The collected data underwent a comprehensive analysis, incorporating a range of techniques: a five-point Likert scale to gauge attitudes, percentage calculations for quantitative insights, graphical representations for visual clarity, flowcharts to illustrate processes, and descriptive analysis to contextualize the findings. The result of the study shows that AI plays a pivotal role in enhancing TSR, TI and WTC. It also explicates the significance of human interaction and human feedback in language teaching due to the ambiguous nature of language.